CLOUD SERVICES IN DISTRIBUTED NETWORK INFRASTRUCTURE - Kyrychek, H. H.; Tseluiko, R. O.; Tiahunova, M. Yu.; Zhyvohliad, V. A. (Systems and Technologies, 2025)
The article considers approaches to implementing cloud services into distributed network infrastructure. An overview of modern platforms (AWS, Microsoft Azure, Google Cloud Platform) and monitoring systems (Prometheus, Grafana) is provided, automation methods and resource scaling algorithms based on events and metrics are described. The main focus is on the implementation and verification of models that ensure dynamic scaling, fault tolerance, and cost optimization. The purpose of the work is to analyze leading cloud platforms, implement and verify a model for managing distributed network infrastructure using cloud services, which provides: centralized monitoring using Prometheus and Grafana; adaptive scaling of resources based on metrics and security of data transmission between local nodes and cloud services. The object of research is the process of integrating cloud technologies into the infrastructure of distributed networks. The subject is software, tools, methods, models for monitoring and managing distributed networks. The authors developed an infrastructure management model using integration with a public cloud. Several load scenarios were simulated and private, public, and hybrid integration models were compared in terms of performance, fault tolerance, and costs. Algorithms for automatic scaling based on Prometheus Alertmanager and AWS Auto Scaling are presented, and a set of practical recommendations for the secure integration of cloud services into distributed networks is proposed. The management system was modeled with the integration of Prometheus and Grafana tools. The results confirm that the integration of cloud solutions and Software-Defined Networking (SDN) methods allows for a significant increase in the performance and resilience of the network infrastructure, which is critical for modern scalable solutions. The results obtained can be used when modernizing corporate network infrastructure to increase its reliability and efficiency. The results showed that as the number of users increases, latency increases, but the system maintains functionality even under peak conditions.